2002
DOI: 10.1002/jctb.726
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic combustion of chlorinated ethylenes over H‐zeolites

Abstract: Several H-zeolites (H-Y, H-ZSM-5 and H-MOR) were investigated for the catalytic combustion of chlorinated ethylenes, namely 1,1-dichloroethylene and trichloroethylene. Conversion was inversely related to the chlorine content of the feed molecule. H-ZSM-5 zeolite was the most active catalyst in 1,1-dichloroethylene combustion whereas H-MOR was the most effective zeolite for trichloroethylene destruction. Temperature-programmed desorption of ammonia and diffuse reflectance FT-IR measurements of adsorbed pyridine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…These conversions were attributed to thermal oxidation and that catalyzed by sites other than silver. These sites were likely to be acid sites that have been widely reported in the literature [6,18]. It could be deduced from the result that the thermal combustion was also negligible below 350 • C and started to be significant at 400 • C. Any improvement in the conversion beyond that caused by thermal oxidation when the metal exchanged HZSM-5 was used could therefore be attributed to the positive effect of the metal.…”
Section: Role Of the Silver In Voc Oxidationmentioning
confidence: 86%
See 3 more Smart Citations
“…These conversions were attributed to thermal oxidation and that catalyzed by sites other than silver. These sites were likely to be acid sites that have been widely reported in the literature [6,18]. It could be deduced from the result that the thermal combustion was also negligible below 350 • C and started to be significant at 400 • C. Any improvement in the conversion beyond that caused by thermal oxidation when the metal exchanged HZSM-5 was used could therefore be attributed to the positive effect of the metal.…”
Section: Role Of the Silver In Voc Oxidationmentioning
confidence: 86%
“…This result indicated that active metal content alone could not result in a good catalyst. Other contributing factors are such as metal dispersion, available surface area, exchange site and other type of active site that could catalyze the reaction such as acid sites [6,8].…”
Section: Catalyst Activity Of Agy and Agzsm-5mentioning
confidence: 99%
See 2 more Smart Citations
“…Several investigations [28][29][30][31][32][33] pointed out that the HC adsorbed on zeolite can be protonated by acid sites and form the carbenium ions, which are in favor of cracking and oxidation. The higher acid strength would cause higher activity of cracking and oxidation for zeolite [34,35]. Due to greater acidity and higher strength of strong acid sites, the coated beta behaves with considerable activity for catalytic 36.0 a): the normalized amount with respect to the weight percent of coating.…”
Section: Analysis With Msmentioning
confidence: 99%